Design, Synthesis, and Insecticidal Evaluation of New Pyrazole Derivatives Containing Imine, Oxime Ether, Oxime Ester, and Dihydroisoxazoline Groups Based on the Inhibitor Binding Pocket of Respiratory Complex I - Song, Hongjian; Liu, Yuxiu; Xiong, Lixia; Li, Yongqiang; Yang, Na; Wang, Qingmin (Journal of agricultural and food chemistry, 2013)
On the basis of complex I receptor protein binding site and commercial tebufenpyrad and tolfenpyrad, four series of novel pyrazole-5-carboxamides containing imine, oxime ether, oxime ester, and dihydroisoxazoline were designed and synthesized via the key intermediate 4-chloro-3-ethyl-N-(4-formylbenzyl)-1-methyl-1H-pyrazole-5-carboxamide. The structures of target compounds were confirmed by 1H NMR and high-resolution mass spectrum (HRMS). The results of bioassays indicated that the target compounds possessed good-to-excellent activities against a broad spectrum of insects such as cotton bollworm (Helicoverpa armigera), spider mite (Tetranychus cinnabarinus), bean aphid (Aphis craccivora), and mosquito (Culex pipiens pallens), but gave different structure–activity relationships for each species. Compounds containing imine showed high insecticidal activity against cotton bollworm. Especially, stomach activity of compounds 5-1c was 60% at 11 mg kg–1. The compounds also had good activities against bean aphid and mosquito. The foliar contact activity of compounds 5-1a, 5-1b, 5-1e, 5-3c, and 5-3d against bean aphid were 90, 100, 90, 90, and 90%, respectively, at 200 mg kg–1. The activity of compound containing dihydroisoxazoline moiety (5-4) against mosquito was 60% at 1 mg kg–1, which was near that of tebufenpyrad. The introduction of dihydroisoxazoline structure (5-4) was advantageous to improve the activity of the compound against adult mites compared with other structures; the miticidal activity of 5-4– against adult mites was 60% at 50 mg kg–1.